The Experience With Flow Diverters in the Treatment of Posterior Inferior Cerebellar Artery Aneurysms. Issue 1 (12th February 2019) - Atallah, Elias; Saad, Hassan; Li, Jonathan; Kumar, Ayan; Tjoumakaris, Stavropoula; Chalouhi, Nohra; Hasan, David; Zarzour, Hekmat; Herial, Nabeel; Gooch, Michael Reid; Rosenwasser, Robert H; Jabbour, Pascal
ABSTRACT: BACKGROUND: The use of the pipeline embolization device (PED; Medtronic, Dublin, Ireland) in the posterior circulation has been limited and infrequently reported compared to other off-label utilizations. Posterior inferior cerebellar artery aneurysms (PICAA) constitute 1 of the least reported posterior circulation aneurysms treated with PED. No clinical studies have addressed the treatment of these aneurysms with flow diversion exclusively. OBJECTIVE: To appraise the feasibility and the safety of PED in the treatment of PICAAs. METHODS: Data on 12 consecutive patients, treated between 2011-2017 with PED for their PICAA, was retrospectively reviewed. To control confounding, we used multivariable logistic regression and propensity score conditioning. RESULTS: Of 534 patients, 12 (9/12, 75% males) were identified and constituted our study population. The average aneurysm size was 8.47 mm (SD = 2.6, 3.7-14). Patients were followed-up for an average of 10.3 months (SD = 11 mo). Two of 12 (16.7%) had a prior history of subarachnoid hemorrhage. Eight of 12 (67%) of the aneurysms were saccular, 3/12 (25%) were dolichoectatic, and 1/12 (8%) was a small blister aneurysm. Eleven of 12 (92%) aneurysms were treated with 1 PED; 2/12 (16.7%) patients received combined pipeline assisted coiling. All patients had a complete occlusion, regression, and resolution of their aneurysm(s). PED deployment was neither complicated with any hemorrhagic or clinically significant thromboembolic events nor with device migration in any of our patients. Three of 12 (25%) patients had a benign intrastent stenosis. No mortality, among our 12 patients, was noted throughout the follow-up period. CONCLUSION: PED, deployed by specialized experts, should be safe in treating PICAA. It can be contemplated as a novel alternative treatment of aneurysms located at the PICA-VA bifurcation or within the PICA.